Tantangan identitas nasional di dunia post-truth: Peran media sosial dalam pembentukan wacana nasional - febrian, zaky maulana (Maliki Interdisciplinary Journal, 2025)
National identity is a crucial element in maintaining social cohesion and the sustainability of a nation, especially amidst the tides of globalization and misinformation in the post-truth era. This study aims to analyze how higher education institutions, particularly the State Islamic University of Maulana Malik Ibrahim Malang (UIN Malang), integrate Islamic values with modern scientific knowledge to strengthen national identity. Using a descriptive-qualitative approach and literature analysis from UIN Malang scholars, the study finds that the curriculum model based on the “tree of knowledge” and the principle of wahdatul ‘ulum (unity of knowledge) serves as a fundamental framework in shaping students with religious, intellectual, and nationalist character. The integration of knowledge grounded in the concept of tauhid not only produces academically competent graduates but also fosters agents of unity in a diverse society. The findings indicate that the integrative approach implemented at UIN Malang can serve as a model for national curriculum development aimed at reinforcing Indonesia’s identity in a global context.